ОЦІНЮВАННЯ ЕФЕКТИВНОСТІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ПОЛІЦЕЙСЬКИХ В УКРАЇНІ - Потопальський, Артем Віталійович (SUPREMANCE OF LAW, 2019)
In the article, based on the analysis of scientific views of scientists and norms of the current legislation of Ukraine, it is emphasized that there is a need to improve and change the format of professional training of police officers, not only does it need to update its mechanism, but also to develop a procedure for evaluating effectiveness, which will serve as an effective tool for identifying problematic issues of departmental training. It is established that the effectiveness of organizational and legal support of police training in Ukraine is an indicator that informs on the degree of achievement of the goal in the implementation of procedures, mechanisms, individual actions, means, legal methods, etc. aimed at providing police professional training, as well as the highest level of consistency. , systematic and stability of the latter. It is substantiated that the effectiveness of police training is characterized by the following features: it is an integral part of the indicator of the effectiveness of the organizational and legal support of the work of the services and units of the National Police as a whole; this indicator not only provides information on the current state of vocational training, but also shows problematic issues that need attention in this area; the effectiveness of the legal support of police professional training is a dynamic and sensitive indicator that may vary depending on the intensity of the use of administrative tools for the provision of departmental training; the indicator of the effectiveness of the legal and professional support of police training needs constant monitoring through evaluation, solely at the expense of which its analysis will benefit. It is generalized that the assessment of the effectiveness of the organizational and legal support ofprofessional training of police officers in Ukraine involves the control of thefollowing questions: whether the level of knowledge, skills and skills of police officers increases after passing the appropriate type ofprofessional training; whether the training programs are in line with current international trends in police training; Does the current legal framework governing the vocational training system provide for the systematic, continuous nature of the latter; quality of organizational measures of subjects providing vocational training on material, technical, functional and other types of providing departmental training; the degree of implementation of the legal requirements for the process of vocational training, both by the subjects of its provision and the addressees of training; the level of awareness and educational level of management, which determines their professional competence and relevance to the position.